Analisis Bottleneck dan Kapasitas Mesin Untuk Meningkatkan Efisiensi Produksi Cup Plastik di PT 'X' - Evelyn Agustin; Daniel Marcello; Muhammad Ferdy Setiawan; Michael Valentino Diamond (Indonesian Journal Publisher, 2025)
This study aims to identify, analyze, and provide solutions to bottlenecks in the plastic cup production process at PT 'X'. The bottleneck caused by static electricity lamps led to a decrease in production efficiency, with a downtime of up to 20 minutes per day and a reduction in capacity by 450,000 cups per month. The Capacity Requirement Planning (CRP) method and cycle time analysis were employed to evaluate machine capacity and identify the root causes of production constraints. After improvements, including the addition of static electricity eliminators, the cycle time was optimized from 0.108 seconds/cup to 0.0864 seconds/cup, downtime significantly reduced to 2 minutes per day, and defective products decreased by up to 80%. Production capacity increased from 2.4 million to 3 million cups per day, meeting the target. This study highlights that eliminating bottlenecks through technological optimization can significantly enhance production efficiency and the company's competitiveness.